Blood memory - McElroy, Colleen J. (Pittsburgh, Pa. : University of Pittsburgh Press, 2016)
Blood Memory, Colleen J. McElroy's collection of narrative poetry, emerges from deep seated memories with enormous emotion. Through the rhythms and musicality unique to McElroy's voice, it portrays an extended family, a complex culture spanning several decades, multiple victories and failures, and a single brilliant soul that frames the poems. Dedicated to McElroy's mother, the book is universal in its scope, inescapable in its earthy particularity. McElroy writes, "I am the last female of a family/ of women who wove the fabric/ of stories into doilies and slip covers.../" Blood Memory offers consummate storytelling and unforgettable poetry capturing a place and time gone forever. And as an evolving history, the poetry has a cinematic quality, large and intimate and at the same time, characters utterly vivid.
The Answers to Why -- The Legacy -- Learning to Love Bessie Smith -- My Mother's Baby Toe -- Did You Ever Have the Feeling -- Chevalier -- Aces and Eights -- Defining Life -- Lessons in Deportment -- The Spinsters -- Breaking Wild Horses -- The Fire Inside -- Missouri Blues -- Throwing Stones at the All White Pool -- Fade to Black -- Double Dutch -- Tongue Tied -- Twilight Sleep -- The Mistress of Secrets -- The Prodigal Daughter -- Lividity -- Did I Know You Back Then? -- The Third Stage -- Blood Lines -- Acknowledgments
JSTOR
Keywords: African Americans -- Poetry; African American women -- Poetry; Noirs américains -- Poésie.; Noires américaines -- Poésie.; POETRY / General; African American women; African Americans; Electronic books; poetry; Poetry; American poetry; Poetry; Poésie.